STATUS OF INFECTIONS WITH LARVA MIGRANTS IN IRAN - F-Arfaa (Tehran University of Medical Sciences, 1972)
Alter a definition of the condition of larva migrants and a description of the types of helminthes which cause this affection in man a brief account of the pathology and clinical manifestations of both visceral and coetaneous larva migrants is given. Studies undertaken in Iran have revealed the presence of most of 1ihe animal helminthes which cause coetaneous larva migrants of the parasites which are responsible for the infection of man with visceral larva migrants, both Toxocara canis and T cati have been reported from various parts of the country. The infection rate for T. canis among dogs varies from 17 to 76% in the areas surveyed. The results obtained indicate that most probably both visceral and coetaneous larva migrant are found among the population in various parts of Iran, and with more attention given to the clinical manifestation and the use of laboratory methods, many cases will be diagnosed.